Atypical deep peroneal neuropathy: In presence of accessory deep peroneal nerve - Gutmann, L. (1970)
The clinical and electrophysiological findings in two patients with a deep peroneal neuropathy occurring in the presence of significant innervation of the extensor digitorum brevis muscle by the accessory deep peroneal nerve are reported. This nerve is a branch of the superficial peroneal nerve which was not involved in either cases reported. An awareness of this anatomical variation of innervation of the extensor digitorum brevis muscle is important for the correct clinical and electromyographic evaluations of deep peroneal nerve lesions. The electromyographic findings in this situation are sufficiently characteristic to identify clearly this anatomical variant. From a clinical point of view, residual function in the lateral portion of the extensor digitorum brevis muscle, in the face of an otherwise complete deep peroneal palsy, should suggest this anatomical variation.